Crossing Laterally into Solidarity in Montserrat Fontes's Dreams of the Centaur - J. Douglas Canfield (Studies in 20th & 21st Century Literature, 2001)
Fontes's novel begins with a corrido announcing typical themes of murder and revenge. But the novel has from the outset been interimplicated in a history of the persecution of the Yoeme (Yaquis) at the turn into the twentieth century. Its three main protagonists become mavericks on the border, as they cross ultimately not only into safety in Arizona but into solidarity with the oppressed. Such crossings are existential, resulting in new identities that eschew racial or ethnic purity but instead embrace mixed ethnicity, or mestizaje (to borrow key concepts from Anzaldúa). Such crossings are lateral, non-hierarchic. But Fontes does not allow refuge in some romantic vision: even as one crosses over, one retains one's membership in the group that oppresses. Instead, Fontes's mavericks—and Fontes herself— become tellers of a story too little known, too horrible to be obliterated. United in a kinán of spiritual force, they become potential "drops of water that penetrate and soften the land," leaving prints for others to follow."
Keywords: Montserrat Fontes; Dreams of the Centaur; Yoeme; Yaquis; border; oppressed; crossing; border narrative; identity; mixed ethnicity; mestizaje; kinán; solidarity; Chicana fiction